MnO2-SnO2 Based Liquefied Petroleum Gas Sensing Device for Lowest Explosion Limit Gas Concentration. (3rd August 2022) - Singh, Ajeet; Verma, Arpit; Yadav, B. C.
Abstract : In this work, MnO2 -SnO2 nanocomposite based below lower exposure limit (0.5–2.0 vol%) sensing device for liquefied petroleum gas (LPG) is reported. The synthesized material is highly crystalline with an average crystallite size of 16.786 nm, confirmed by the X-ray diffraction pattern. Williamson-Hall plot shows that the induced strain of 2.627 × 10 −4, present in the nanocomposite, lies between the induced strains of both of its constituents. The XRD pattern of nanocomposite contains the cubic phase of MnO2 and the tetragonal phase of SnO2 . Tauc plot shows the optical energy band gap of MnO2, SnO2, and MnO2 -SnO2 of 3.407 eV, 3.037 eV, and 3.202 eV respectively. The surface morphological investigation shows the brush-like structure which enhances sensor performance by providing activation sites. The energy dispersive X-ray (EDS) spectrum found that materials are highly pure because other peaks are not observed. The functional group analysis by using FTIR found to be Sn–O and Mn–O both vibration bands existed. The highest sensor response was found to be 2.42 for 2.0 vol% whereas for a lower concentration of 0.5 vol% the sensor response was observed to be 1.44. The fast response and recovery of this sensing device were found to17.30 and 23.25 s respectively for 0.5 vol% of LPG.